Validity of Self-perceived and Clinically Diagnosed Gingival Status among 12-15-year-old Children in Indonesia - Robbykha Rosalien; Frida Avianing Isnanda Saragih; Ary Agustanti; Febriana Setiawati; Diah Ayu Maharani (JMIR Publications, 2019)
A few studies have revealed the self-perceived gingival status using questionnaires among children. Perceived health is a crucial factor that has an impact on quality of life. The objective of the study was to assess self-perceived and clinically diagnosed gingival status among children in Indonesia. This was a cross-sectional study of 494 schoolchildren (aged 12-15 years). Periodontal status was recorded using the gingival index (GI) and plaque index (PI) based on the World Health Organization standards. Data were collected through a brief visual, noninvasive clinical oral examination and a self-administered questionnaire. The sensitivity and specificity of self-perceived assessment were calculated using normative assessment as the gold standard. This study showed that self-perceived need for dental treatment showed the highest sensitivity (86% using PI and 85% using GI) and self-perceived swollen gums showed the highest specificity (89% using PI and 88% using GI) for clinically diagnosed plaque (PI cut-off value: 0.74) and gingival problems (GI cut-off value: 0.51). In conclusion, both self-perceived variables showed significant discordance between their respective sensitivity and specificity. Self-perceived information is at a higher-level unawareness that does not reflect the current gingival status. Thus, public health strategies are needed to improve the awareness of better oral health among children by promoting, empowering, and advocating.